KARAKTERISTIK ENDAPAN GUNUNG GEDE KAITANNYA DENGAN KETERDAPATAN AIRTANAH UNTUK KEPERLUAN MASYARAKAT DAERAH GEKBRONG KABUPATEN CIANJUR - -, Undang Mardiana; -, Febriwan Mohamad (Fakultas Teknik Geologi Universitas Padjadjaran, 2009)
Administratively, Gekbrong area included into Kabupaten Cianjur region; this area is frontier between Kabupaten Cianjur ( Gekbrong) with Kabupaten Sukabumi ( Cimangkok), resides in Cianjur – Sukabumi roadside. Morphologically as centered bevel of Gunung Gede (Volcano mount foot geomorphology set) with inclination bevel of between 5 - 45 % and height between 400 - 1400 meter asl. River drift pattern grows in this area is sub-parallel pattern which mains to Cibeleng river, with relative Northwest – Southeast stream direction. Geology of this area compiled by pyroclastic and laharic rock; consisted of breccia, tuff, lapilli and laharic breccia from Gunung Gede, while laying below it are compilation between Cantayan Formation Breccias component with Upper Miocene age (Mttb), Cantayan Formation Claystone component with Upper Miocene age (Mttc), Resulting Deposit Of Eldest Volcano ( Qot) Early Plistocene age and Mount Gede Lava ( Qyl) Mid Plistocene age, Breccias and lava of Mount Gede ( Qyg) Late Plistocene age (Cianjur Sheet Geological Map; Sudjatmiko, 1972).Geoelectric investigation done on the basis of physical rock properties to electric current, where each different rock will have different resistivity value. This consideration depends on some factors, such as rock age, electrolyte content, rock solidity, number of minerals contained, porosity, permeability and others. Mostly applied geophysical exploration method in subsurface hydrogeology investigation is geoelectric method (resistivity method). This sounding type also called as Vertical Electric Sounding ( VES), aimed to study various rock resistivity to vertical depth below measuring points (measuring point).Geoelectric investigation result show that there are three rock packages based on distribution and contrast of resisivity value which are interval between rugged and fine clastic and shows more laharik process after compared to its geology condition, such as :a.First package is the topmost package which is phyroclastic rock found at interval depth of 0 until - 30 meter with resistivity value of < 50 Ω m , 50 - 100 Ω m and 100 - 150 Ω m. b.Second package, being volcanic rock package found at interval depth of 0 until - 30 meter with resistivity value of < 50 Ω m, 50 - 100 Ω m and 100 - 150 Ω m. c. Third package start t at - 100 meter depth, compiled by rock with resistivity value between 40 - 50 Ω m (lapilian tuff) and 50 - 100Ω m (lapillian matrix supported breccias).